When Children Become Adults: Should Biobanks Re-Contact? - Giesbertz, Noor A. A. (PLoS Med, 2016)
Noor Giesbertz and colleagues consider different re-contact policy designs that could be used by biobanks to obtain permission for the continued use of samples collected from children.